Modeling Human Antitumor Responses In Vivo Using Umbilical Cord Blood-Engrafted Mice - Zumwalde, Nicholas A.; Gumperz, Jenny E. (Frontiers in Immunology, 2018)
Mice engrafted with human immune cells offer powerful in vivo model systems to investigate molecular and cellular processes of tumorigenesis, as well as to test therapeutic approaches to treat the resulting cancer. The use of umbilical cord blood mononuclear cells as a source of human immune cells for engraftment is technically straightforward, and provides T lymphocytes and autologous antigen presenting cells (including B cells, monocytes, and DCs) that bear cognate antigen presenting molecules. By using a human-specific oncogenic virus, such as Epstein-Barr virus, de novo neoplastic transformation of the human B cells can be induced in vivo in a manner that models progressive stages of tumorigenesis from nascent neoplasia to the establishment of vascularized tumor masses with an immunosuppressive environment. Moreover, since tumorigenesis occurs in the presence of autologous T cells, this type of system can be used to investigate how T cells become suppressed during tumorigenesis, and how immunotherapies counteract immunosuppression. This minireview will provide a brief overview of the use of human umbilical cord blood transplanted into immunodeficient murine hosts to model anti-tumor responses.